Rubber Compounding and Processing Laboratory - Naval Air Experimental Station; United States. Navy (1949)
General view of the Rubber Compounding and Processing Laboratory at the Naval Air Experimental Station's Aeronautical Materials Laboratory. Two workers and an assortment of machinery and scientific apparatus, including mixers, extruders, and hydraulic presses, are visible in the photograph, which was included in a 1949 Naval Air Experimental Station report on compounding rubber. The primary purpose of the laboratory was the production of various molded, extruded, and sheeted rubber parts used in assorted aircraft applications.
Keywords: Aerospace Research Laboratories (U.S.); Employees; Rubber; Naval Research Laboratory (U.S.); Machinery